Pengaruh Opini Audit dan Cash Flow terhadap Harga Saham dengan Ukuran Kantor Akuntan Publik sebagai Variabel Moderasi - Hidayatullah, Muhammad Iqbal; Muanifah, Suciati (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research aims to empirically prove the Influence of Audit Opinion and Cash Flow on Stock Prices with the Size of Public Accounting Firm as a Moderating Variable. In this study, the independent variables used are Audit Opinion and Cash Flow, while the dependent variable used is Stock Price, and the moderating variable used is the Size of Public Accounting Firm. The research was conducted by sampling Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The type of data used in this study is secondary data in the form of audited financial reports published on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Samples were collected using purposive sampling method with a total of 30 companies as samples over a 5-year research period, resulting in 150 company samples. Data processing was done using Microsoft Office Excel and Eviews 12 Statistical Program by analyzing descriptive statistics, model suitability tests, classical assumption tests, coefficient of determination, panel data regression analysis, F-statistic tests, t-statistic tests, and moderation tests. The results of this study indicate that: (1) Audit Opinion and Cash Flow simultaneously influence Stock Prices, (2) Audit Opinion significantly influences Stock Prices, (3) Cash Flow does not affect Stock Prices, (4) the Size of Public Accounting Firm is unable to moderate the influence of Audit Opinion on Stock Prices, (5) the Size of Public Accounting Firm is unable to moderate the influence of Cash Flow on Stock Prices.